2001
DOI: 10.1152/ajplung.2001.281.2.l418
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between CBP, NF-κB, and CREB in the lungs after hemorrhage and endotoxemia

Abstract: The transcriptional regulatory factor nuclear factor (NF)-κB has a central role in modulating expression of proinflammatory mediators that are important in acute lung injury. In vitro studies have shown that competition between NF-κB and cAMP response element binding protein (CREB) for binding to the coactivator CREB-binding protein (CBP) is important in regulating transcriptional activity of these factors. In the present study, we examined in vivo interactions between CBP, CREB, and NF-κB in hemorrhage- or en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…Immunohistochemistry of phosphorylated Erk1/Erk2 (e) and phosphorylated CREB (f, g) in lung tumor T2 (e, f) and T4 (g). Immunohistochemistry was performed as described in Figure 1 using a 1 : 100 dilution of the primary antibodies activated in lungs in response to insults such as hemorrhage (Shenkar and Abraham, 1999;Abraham et al, 2001;Shenkar et al, 2001), endotoxemia (Shenkar and Abraham, 1999;Abraham et al, 2001;Shenkar et al, 2001), hyperoxia (George et al, 1999) and metal exposure (Samet et al, 1998) and is important for normal lung development (Rudolph et al, 1998), its role in lung tumorigenesis has not been reported.…”
mentioning
confidence: 99%
“…Immunohistochemistry of phosphorylated Erk1/Erk2 (e) and phosphorylated CREB (f, g) in lung tumor T2 (e, f) and T4 (g). Immunohistochemistry was performed as described in Figure 1 using a 1 : 100 dilution of the primary antibodies activated in lungs in response to insults such as hemorrhage (Shenkar and Abraham, 1999;Abraham et al, 2001;Shenkar et al, 2001), endotoxemia (Shenkar and Abraham, 1999;Abraham et al, 2001;Shenkar et al, 2001), hyperoxia (George et al, 1999) and metal exposure (Samet et al, 1998) and is important for normal lung development (Rudolph et al, 1998), its role in lung tumorigenesis has not been reported.…”
mentioning
confidence: 99%
“…It has been suggested that the bromodomain recognizes acetylated residues and could function in identification of different acetylated domains. The CH domains and the (142,147).…”
Section: Role Of Cbp In Cxcl1 Transcriptionmentioning
confidence: 99%
“…The CH domains and the KIX domain are thought to mediate protein-protein interaction (146). The KIX domain is involved in the interaction between CBP and the p65 (Rel A) subunit of NF-κB, as well as CBP binding to the transcriptionally active serine-133-phosphorylated form of CREB (142,147).…”
Section: Role Of Cbp In Cxcl1 Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations